Hypothyroidism Increases 90-Day Complications and Cost Following Primary Total Hip Arthroplasty - Damodar, Dhanur; Vakharia, Ajit; Zachwieja, Erik; Vakharia, Rushabh; Hernandez, Victor; Roche, Martin W. (The Journal of Hip Surgery, 2019)
Hypothyroidism is common, and the incidence has been increasing annually in the United States. Abnormalities in thyroid hormone can have several effects on the endocrine, immune, and musculoskeletal systems of the body. The influence of hypothyroidism on outcomes following primary total hip arthroplasty (THA) is not well reported. The authors hypothesized that hypothyroidism was associated with a higher risk of postoperative complications and 90-day costs following primary THA. A retrospective review from 2005 to 2014 was performed using the Medicare Standard Analytical Files from the Pearl Diver database. Utilizing International Classification of Disease 9th revision (ICD-9) codes, the authors identified patients who underwent THA. Patients with a concurrent diagnosis of hypothyroidism were matched by age, gender, and Charlson's comorbidity index (CCI) to a control group. Ninety-day postoperative complications, readmission rates, complications related to implants, and cost of care were compared and assessed following primary THA between matched cohorts. Statistical analysis was performed using the programming language R (University of Auckland) to calculate odds ratios (OR) along with their respective 95% confidence intervals (95% CI), and p-values. A total of 383,898 patients underwent primary THA. Among them, 191,949 patients were diagnosed with hypothyroidism and 191,949 patients without hypothyroidism. Hypothyroidism was associated with greater odds of postoperative complications (p < 0.001), 90-day readmission rates (p < 0.001), implant related complications (p < 0.001), and total global 90-day episode of care cost (U.S. $17,549.96 vs. $16,645.01; p < 0.001). This study demonstrated an increased risk of postoperative complications (medical or implant related), increased readmission rates, and higher costs among patients with hypothyroidism following primary THA. Surgeons should counsel patients and determine strategies to medically optimize patients to mitigate risk and decrease cost.
Keywords: total hip arthroplasty outcomes; Medicare; complications; hypothyroidism; database